The degree of school principals’ practice of distributive leadership and its relationship to achieving organizational excellence: An applied study in public secondary schools in the capital Amman governorate - Ammari, Suhair Hani (Journal of Educational and Psychological Sciences, 2022)
The study aimed to identify the degree of distributive leadership practice by public secondary school principals in the capital Amman governorate and its relationship to their level of organizational excellence. The correlative descriptive approach was used. The researcher used the questionnaire as a tool for the study. The results showed that the degree of distributive leadership practice by public secondary school principals in the capital Amman governorate from the teachers’ point of view was high, with an arithmetic average of (4.20). Furthermore, the level of organizational excellence among public secondary school principals in the capital Amman governorate from the teachers’ point of view was high as well. With a mean of (4.25). The results also showed that there was of a positive, statistically significant, correlation between the degree of distributive leadership practiced by secondary government school principals in the Amman governorate and their level of organizational excellence. The study recommended encouraging school principals to practice distributive leadership for its clear impact on achieving excellence in school performance and achieving organizational excellence Moreover, the need for school principals to expand the powers of teachers and delegate them to carry out leadership tasks commensurate with their abilities and qualifications.
Keywords: Distributive leadership; organizational excellence